Hubungan Kebiasaan Sarapan Pagi Dengan Prestasi Belajar Pada Siswa SDN 1 Batuah Kecamatan Kusan Hilir Kabupaten Tanah Bumbu - Akhmad Murjani; Abd Basid; Mega Hardiyanti (HB PRESS, 2018)
Background,There are still many children who have not get used to themselves with breakfast. Berides not having breakfast, will have a negative impact on the learning proses. Breakfast will provides the body with the necessary nutrients and that’s proven to increase learning concentration. The number of malnourished children in Indonesia is still high than the threshold set by WHO. Nutrional status on KusanHilir sub district in 2017 is in the category of BB / U, TB/ U, TB/ U, and BB / TB there are 366 cases. This study aims to determine the relation between breakfast habits with learning achievement in students at Batuah 1 Elemantary School Sub District Kusan Hilir Tanah Bumbu Regency. Method, this study uses an analytic observational method with a cross sectional approach. This reseaech was conducted at Batuah 1 Elementary School KusanHilir sub district. The study population was all students of class III, IV and V with a total sample of 61 respondents using probability sampling technique. Research variables included breakfast habits and learning achievement. Data on breakfast habits using questionnaires and learning achievement of report books. Statistical test using Spearman’s Rank Test.Result, this study shows that respondents who have good breakfast habits are 7 (11%) and respondents have good learning achievement 39 (64%). The conclusion of this study, there is a significant relations between the habit of breakfast with learning achievement in students at SDN 1 Batuah Sub district KusanHilir, regency Tanah Bumbu.